Sleep in elite multi-sport athletes: Implications for athlete health and wellbeing. (September 2019) - Biggins, Michelle; Purtill, Helen; Fowler, Peter; Bender, Amy; Sullivan, Kieran O.; Samuels, Charles; Cahalan, Roisin
Abstract: Objectives: To investigate the prevalence of clinically relevant sleep problems in elite multi-sport athletes and their associations with sleep hygiene, general health, mood, chronotype, and injury. Design: Cross-sectional study. Setting: During the competitive season in athletes' home environment. Participants: Elite multi-sport Irish athletes (n = 58) competing at the 2017 World University Games. Main outcome measures: Category of clinical sleep problem (Athlete-Sleep-Screening-Questionnaire), sleep hygiene (Sleep Hygiene Index), general health (Subjective Health Complaints), mood (Sports Profile of Mood States), chronotype (Morningness-Eveningness Questionnaire), and injury (self-reported injury). Results: 43% had no clinical sleep problem, 41% had a mild clinical sleep problem, 16% had a moderate clinical sleep problem, none had a severe clinical sleep problem. Therefore, 84% of athletes did not have a clinically significant sleep problem while 16% had a clinically significant sleep problem. One-way-ANOVA revealed significantly worse sleep hygiene (p = 0.002), more general health complaints (p = 0.001) and greater mood disturbance (p = 0.001) among those with clinically significant sleep disturbances compared to those without. No association was found between having a clinically significant sleep problem and either chronotype or previous recent injury. Conclusions: Athletes with a clinically significant sleep problem were more likely to report worse sleep hygiene, more general health complaints, and mood disturbance. Highlights: Sleep screening tools identify athletes with clinically significant sleep problems. Mood disturbance in elite athletes linked with poor sleep. Sleep problems in elite athletes linked with greater health complaints. Poor sleep hygiene is related to significant sleep problems in elite athletes.